DINAMIKA NILAI-NILAI BUDAYA DAN PREFERENSI PRODUK HALAL DALAM PASAR GLOBAL - Hidayatul Istiqomah, Nur; Ghofir, Jamal; Alya Dwi Imaroh, Putri (Department of Da'wah Management, Faculty of Da'wah, IAINU Tuban, 2024)
Rapidly increasing demand for halal products in the global market indicates significant changes in consumer behavior, with consumers increasingly considering halal aspects in their purchasing decisions. Cultural values such as religious beliefs, family traditions, and social norms play a crucial role in shaping consumer preferences for halal products. This research employs library research methods to explore how these cultural values influence consumer behavior and the marketing strategies of halal products in an increasingly interconnected global market. The aim of this study is to analyze the dynamics of cultural values and consumer preferences towards halal products and to explore its strategic implications for the halal industry in the global market. Findings indicate that adapting marketing strategies that are sensitive to cultural diversity and local values is key to gaining consumer trust across different countries. The implications of this research for the industry underscore the importance of understanding and respecting local cultural values in developing halal products and formulating policies that support growth in an increasingly complex and diverse global market. Thus, this study makes a significant contribution to understanding the dynamics of the halal products market in an increasingly interconnected era of globalization.